(untitled) (Annals of Medical Research, 2021)
Aim: Sarcoidosis is a multisystemic disease with typical or atypical pulmonary and extra-pulmonary symptoms or frequently without symptoms. Presence of typical clinical findings and symptoms contribute to rapid diagnosis, whereas asymptomatic progression leads to delays in the diagnosis. The aim of this study was to investigate the delay in diagnosis in between patients with pulmonary and/or extra-pulmonary involvement and related symptoms and those without symptoms. Material and Methods: Patients in the sarcoidosis clinics between 2010-2015, were retrospectively evaluated. The cases were grouped according to the presence or absence of symptoms (pulmonary and/or extra-pulmonary). The groups were compared with regard to the delay in diagnosis. Results: Among the 300 patients, 209 (69%) were female. The mean age was 43±11.68. The disease was stage I in 67.3%, stage II in 23.7%, stage III in 5.7% and stage 0 in 3.3% of the patients. No significant difference was observed between symptomatic and asymptomatic patients with regard to total duration until diagnosis (p=0.78). A statistically significant difference was observed between patients groups with regard to physician-related delayed diagnosis(p=0.026). The mean delay in physician-related diagnosis was observed to be longer in asymptomatic cases (21.44 days) compared to patients with pulmonary symptoms (13.66 days)(p=0.036). In asymptomatic cases, the mean duration of physician-related delayed diagnosis (21.44 days) was observed to be longer in comparison with patients with extra-pulmonary symptoms (12.79 days)(p=0.016). In patient-related delayed diagnosis, no difference was observed between groups with regard to the duration until diagnosis(p=0.78). Conclusion: Comparison of delayed diagnosis between patients with or without pulmonary and/or extra-pulmonary symptoms revealed a longer duration of delay in asymptomatic cases compared to symptomatic cases. The timing of diagnosis is very important in sarcoidosis in order to reduce morbidity and mortality; a suspicious approach to asymptomatic patients will increase the possibility of diagnosis and prevent delayed diagnosis.Keywords: Sarcoidosis; diagnosis; delay; extrapulmonary symptoms.